Evaluation of indirect indices in the insulin resistance assessment in patients with different body mass index - Lejla Čano Dedić; Arzija Pašalić; Emsel Papić; Emir Begagić; Sabina Šečić Selimović; Mario Gazibarić; Sabina Šegalo (Journal of Health Sciences)
Introduction: Insulin resistance (IR) is a complex pathophysiological condition with multifactorial etiology characterized by a reduced responsiveness of target tissues to insulin (INS). Indirect indices based on mathematical models and derived from laboratory parameters have become increasingly popular in the past two decades. In this study, we evaluated their ability to predict IR in a population with different body mass index (BMI).